In memorium Ernests Foldāts (1925.g.15.maijs-2003.g.15.janvāris) - Kondratovičs, Rihards (My University, 2003)
Latviešu biologa Riharda Kondratoviča sarakstīts latviešu orhideju pētnieka Ernesta Foldāta nekrologs. Rakstīts par Foldāta dzīves gājumu, iegūto izglītību, zinātniskajiem sasniegumiem, akadēmiskajiem amatiem, atklātajām orhideju sugām, iegūtajiem apbalvojumiem, sakariem ar Latviju. Drukāts uz 2 lapām, apakšā Riharda Kondratoviča paraksts. Glabājas Latvijas Universitātes Muzeja Botānikas un mikoloģijas kolekciju krājumā.

Obituary for Latvian orchid researcher Ernesto Foldats, written by Latvian biologist Rihards Kondratovičs. Includes information about Foldat's life, education, scientific achievements, academic positions, discovered orchid species, awards, and contacts with Latvia. Printed on 2 pages, signature of Rihards Kondratovičs at the bottom. Stored in the Museum of the University of Latvia Botanical and Mycological collections.
In memorium Ernesto Foldats (May 15, 1925-January 15, 2003)
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Ernests Foldāts; Ernesto Foldat; nekrologs; in memorium; obituary; orhidejas - Venecuēla; orchids - Venezuela